Learning Evaluation Analysis at SDN 101768 Jalan Besar Tembung, Hutan, Percut Sei Tuan Subdistrict - simanjuntak, roriana mirnawati (Universitas Pendidikan Indonesia (UPI), 2024)
Evaluation is one of the most crucial things to do in learning. Learning evaluation is a continuous and systematic process for assessing student learning progress. Evaluation helps teachers to find out the extent to which learning success improves the quality of learning as expected and provides feedback between teachers and students when the learning proses is underway. There are several kinds of evaluation methods that can be given and carried out by teachers, namely tests, observations, projects and portfolios. The evaluation process also to take into account the uniqueness and needs of each individual. Apart from that, evaluation also aims to collect student information regarding student progress, development and achievements in the learning process. This research was carried out at SDN 101768 Jalan Besar Tembung, Hutan, Percut Sei Tuan District. The purpose of thi research is to find out the evaluatiom carried out by teachers on students during the learning process. In line with the objectives, this research used a qualitative approach with interview and observation methods. Researchers interviewed several teachers to obtain information in the field.